New paleomagnetic results from Blind River: Revised magnetostratigraphy and tectonic rotation of the Marlborough region, South Island, New Zealand - Turner, G.,; Roberts, A.,; Laj, C.; Kissel, C.; Mazaud, A.; Guitton, S.; Christoffel, D. (New Zealand Journal of Geology and Geophysics, 2012)
International audience